Erythema annulare centrifugum: a case report - Thokchom Nandakishore; S., Mrudula; Linda Kongbam; Deepa Yumnam; Shivam Sabharwal; Ruopfükhrietuo Tetso (International Journal of Research in Medical Sciences, 2023)
Erythema annulare centrifugum (EAC) is a rare cutaneous disease characterized by polycyclic lesion simulating urticarial papules that enlarge centrifugally with central clearing and trailing scales. . It is classified as a reactive erythema and has been associated with various underlying conditions, including malignancies. Diagnosis is established on history, clinical features, and supporting examination. No treatment seems to be effective for this disease and there is still a lack of consensus regarding the best approach. Current choices are focused on treating the underlying subjective complaints. We reported a case of erythema annulare centrifugum in a 49 year old female patient.